Rôle et évolution du rôle logistique des lixae dans les armées romaines - Houle, Simon (Université de Montréal, 2016)
This research aims to clarify the lixae’s logistic role in the Roman armies and it evolution between the end of the Republican period and the Late Empire. Although the lixae are often associated with sutlers and camp-followers, their presence in the armies is not limited to these two roles. This research will first define the civilian context in the Roman armies in relation with the lixae. The etymology and historiography of the lixae will then be treated prior to the description and analysis of their different roles according to ancient sources. The last part of this research will focus on the changing role of lixae in the Roman armies. The hypothesis advanced in this research is that the merchant role of lixae in the armies becomes more specialized over time. Finally, all the ancient sources mentioning lixae are grouped in two catalogs in the appendix of this research.
Keywords: Armée romaine; History - Ancient / Histoire - Ancienne (UMI : 0579); Lixa; Logistic in Roman armies; Logistique des armées romaines; Roman army